Effect of cerium salt-activated ceria on the UV degradation resistance of waterborne epoxy coatings - Nguyen, Thuy Duong; Thai, Thu Thuy; Nguyen, Anh Son (Vietnam Journal of Science and Technology, 2020)
Ce (III) salt-activated CeO2 nanoparticles were incorporated into waterborne epoxy coating to improve the UV stabilisation of epoxied system. The surface morphology of the coatings was examined by using color spectrophotometer during the UV exposure test. The degradation of the epoxycoatings was observed by the change of barrier property determined by electrochemical impedance spectroscopy. The effect of activated nanoparticles on the impact resistance and adherence properties was also evaluated by impact strength test and cross-cut test. The results showedthat the epoxy coating with the presence of Ce3+/CeO2 nanoparticles loss only 9.5 % discoloration compared to the non-aged coatings. After 28 cycles of UV test, the barrier property of this coating can be maintained at high impedance module valueat low frequency. The epoxy-Ce3+/CeO2 also presented a good impact strength value, 160 kg.cm, at the end of UV test. On the other hand,the presence of the inorganic compound in the epoxy matrixdid not affect to adherence property of polymer system before or after UV irradiation exposure test.